Peran Disiplin Kerja Sebagai Variabel Moderating pada Pengaruh Pelatihan dan Penempatan Kerja Terhadap Kinerja Pegawai Bappeda Litbang - Indri Mayasari; Mikial; Ima Andriyani; Agustina Marzuki (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to examine the effect of training and job placement on employee performance with work discipline as a moderating variable at the Regional Development Planning, Research, and Development Agency of Banyuasin Regency. The research employs a quantitative approach using a census method, involving all 77 employees of Bappeda Litbang Banyuasin Regency as respondents. Research data were collected through Likert-scale questionnaires and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with the assistance of SmartPLS version 3.0 software. The results indicate that training and job placement have a positive and significant effect on employee performance. Work discipline is also proven to have a positive and significant effect on employee performance. However, the moderation effect testing shows that work discipline does not moderate the relationship between training and employee performance, nor between job placement and employee performance. These findings suggest that improvements in employee performance are primarily influenced by the direct effects of training, job placement, and work discipline itself, without the role of work discipline as a moderating variable in the relationship among these variables.